Whole genome sequencing of metastatic colorectal cancer reveals prior treatment effects and specific metastasis features - Pauline A. J. Mendelaar (Nature Portfolio, 2021)
Molecular landscapes of metastatic colorectal cancers (mCRC) have often been restricted to coding regions or low numbers of patients. Here the authors present a whole-genome landscape of 429 mCRC patients, revealing the mutational impact of prior therapies and potential actionable targets.